1992
DOI: 10.1111/j.1365-2672.1992.tb04993.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the sensitivity of wound‐infecting species of bacteria to the antibacterial activity of manuka honey and other honey

Abstract: Both honey and sugar are used with good effect as dressings for wounds and ulcers. The good control of infection is attributed to the high osmolarity, but honey can have additional antibacterial activity because of its content of hydrogen peroxide and unidentified substances from certain floral sources. Manuka honey is known to have a high level of the latter. Seven major wound-infecting species of bacteria were studied to compare their sensitivity to the non-peroxide antibacterial activity of manuka honey and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(148 citation statements)
references
References 17 publications
10
136
0
2
Order By: Relevance
“…The authors thank factors including the osmotic effect of honey [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], Dr. Harrats Ch. (University of Oran, Algeria) for the the presence of hydrogen peroxide, non peroxide English correction.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…The authors thank factors including the osmotic effect of honey [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], Dr. Harrats Ch. (University of Oran, Algeria) for the the presence of hydrogen peroxide, non peroxide English correction.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Conifer honeydew honey, with exceptionally high activity, was reported to contain a heatstable as well as a heat-sensitive antibacterial factor [50J. More direct evidence for the existence of antibacterial factors additional to hydrogen peroxide is seen in reports of activity persisting in honeys treated with catalase to remove the hydrogen peroxide activity [57,59,72,[78][79][80][81][82]. In one of these studies where substantial antibacterial activity remained it was shown by direct assay of the level of hydrogen peroxide present that the catalase had been completely effective [59J.…”
Section: Additional Antibacterial Factorsmentioning
confidence: 96%
“…Anti-bacterial effect of honey is explained through osmotic effect of its high sugar content, hydrogen peroxide activity (Molan, 1992), additional non-peroxide anti-bacterial factors (Allen, 1991) and low pH, which prevents growth of many organisms. Apart from all these, honey shows immune-stimulant activity by stimulating the mutagenesis of human T-and Blymphocytes and by activating the neutrophils (Abuharfeil, 1999).…”
Section: Effect Of Treatment On the Antimicrobialmentioning
confidence: 99%
“…It has been used topically in the ethno-medicine of the Indian subcontinent since 2500 B.C., and also by the Egyptians, Greeks, and Romans (Ransome, 1987;Gunther, 1959;Zumla, 1989;Molan, 1992;White, 1975;Taormina et al, 2001;Allen, 1991). The most remarkable discovery was the antibacterial activity of honey (Zumla, 1989;Efem et al, 1992;Cooper, 1992;Willix et al, 1992).…”
Section: Introductionmentioning
confidence: 99%